2022
DOI: 10.3390/ijms23137202
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NSE-4 Perturbs Genome Stability and DNA Repair in Caenorhabditis elegans

Abstract: The Structural Maintenance of Chromosomes (SMC) complex plays an important role in maintaining chromosome integrity, in which the SMC5/6 complex occupies a central position by facilitating mitotic and meiotic processes as well as DNA repair. NSE-4 Kleisin is critical for both the organization and function of the SMC5/6 complex, bridging NSE1 and NSE3 (MAGE related) with the head domains of the SMC5 and SMC6 proteins. Despite the conservation in protein sequence, no functional relevance of the NSE-4 homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…The SMC-5/6 complex is made up of the final SMC proteins SMC-5 and SMC-6, a kleisin NSE-4, and up to five regulatory proteins (see Table 4) [70,71]. Generally, the SMC-5/6 complex functions in DNA replication, DNA repair, and silencing of extra-chromosomal DNA [72,73]. In C. elegans, it has been shown that the SMC-5/6 complex processes double-stranded breaks in meiosis and prevents ectopic recombination [74].…”
Section: Structural Maintenance Of Chromosome Proteins Are the Backbo...mentioning
confidence: 99%
“…The SMC-5/6 complex is made up of the final SMC proteins SMC-5 and SMC-6, a kleisin NSE-4, and up to five regulatory proteins (see Table 4) [70,71]. Generally, the SMC-5/6 complex functions in DNA replication, DNA repair, and silencing of extra-chromosomal DNA [72,73]. In C. elegans, it has been shown that the SMC-5/6 complex processes double-stranded breaks in meiosis and prevents ectopic recombination [74].…”
Section: Structural Maintenance Of Chromosome Proteins Are the Backbo...mentioning
confidence: 99%